Clinical development of immunotherapy for prostate cancer. (21st June 2017) - Noguchi, Masanori; Koga, Noriko; Igawa, Tsukasa; Itoh, Kyogo
Abstract: Prostate cancer is the most common cancer in men, and the second leading cause of cancer‐related death in Western countries. Prostate cancer‐related death occurs in patients with metastatic castration‐resistant prostate cancer. Although several new drugs for castration‐resistant prostate cancer have been approved, each of these has prolonged survival by just a few months. Consequently, new therapies are sorely needed. Recently, it has been recognized that immunotherapy is an effective treatment for prostate cancer patients. Several strategies, such as cancer vaccines and immune checkpoint inhibitors, have been investigated in clinical studies for prostate cancer patients. In the present review, the results of the most recent clinical studies investigating immunotherapy in prostate cancer patients are reported, and the future clinical development of immunotherapy for prostate cancer is discussed.